Polyhydroxyalkanoates: A short tale from polymer synthesis to future prospects - de Paula, Fabrício C. [UNESP]; de Paula, Carolina B. C. [UNESP]; Contiero, Jonas [UNESP] (My University, 2018)
Polyhydroxyalkanoates (PHAs) are bacterial polyesters belonging to the most important group of bio-based and biodegradable polymers. A large number of bacteria possesses the ability to synthesize PHAs as carbon energy storage and a variety of monomer constituents of PHAs has been described, whose chemical composition range from straight to aromatic structures. The PHA synthesis is strongly influenced by the carbon source utilized for microbial growth and the metabolic pathways involved in the polymer synthesis, which the PHA synthase plays an essential role in the PHA polymerization process. This chapter introduces PHAs from their biochemical concept to a promising alternative for petrochemical compounds as eco-friendly thermoplastics. Among many suitable characteristics for industrial applications the most important attribute of PHAs is their biodegradability. The challenges faced by the industry of biopolymers in order to scaling-up the PHA production and increase their economical feasibility in the global market, including recent advances to minimize costs and to improve the polymer yield, besides the sustainable production of PHAs from agroindustrial by-products are also a focus of this review chapter.
Keywords: Biodegradable polymer; Biopolymer; Eco-friendly thermoplastic; Microbial polyesters; Polyhydroxyalkanoates